‘Despite the special bonds that tie us’: Portugal, Brazil, and the South Atlantic in the late Cold War (1986-1988) - Seabra, Pedro (18th Annual Conference of the Transatlantic Studies Association (TSA), 2019)
As the Cold War entered the mid-1980s, concerns over the Brazilian nuclear program lingered on through world stages. In this context, Brazil’s proposal for a Zone of Peace and Cooperation in the South Atlantic (ZOPACAS) in 1986 emerged as an opportunity to recast the country’s external profile. Yet, unexpected reservations emerged from the unlikeliest of partners, Portugal. I argue that misperceptions over Brazil's nuclear ambitions factored into Lisbon’s initial positioning as part of broader Western concerns, but that once changes in Portugal, in the region, and in the world occurred, so did the official predisposition towards such a project.